(Why) are immigrants unhappy? - Zsóka Kóczán (IZA Journal of Migration, 2016)
Recent studies suggest that migrants may be less satisfied with their "new" lives than members of the host population and worry that this may be driven by cultural factors, such as feelings of not belonging. Motivated by this concern, this paper analyses the life satisfaction of immigrants once settled in the host country. We rely on the German Socio-Economic Panel's immigrant sample for the years 1984-2010 and find that while immigrants are less satisfied than natives, this difference can be explained by factors related to economic integration, such as the details of their employment conditions, rather than cultural factors such as feelings of not belonging, which often loom large in the public mind.
Keywords: J15; K37; O15; 330; Integration; Subjective well-being; Segregation; Citizenship law